2016
DOI: 10.1007/s10096-016-2799-1
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of cefazolin inoculum effect-positive methicillin-susceptible staphylococcus aureus infection in a multicentre bacteraemia cohort

Abstract: Cefazolin treatment failure has been observed in high-inoculum infections caused by methicillin-susceptible Staphylococcus aureus (MSSA) with a cefazolin inoculum effect (CIE). However, data on the characteristics and risk factors for the acquisition of CIE-positive MSSA infection are scarce. CIE positivity was measured as an MIC ≥ 16 μg/ml with a high inoculum (∼5 × 10 CFU/ml). The blaZ gene type was assessed through sequence analysis. The clinical characteristics and risk factors for the acquisition of CIE-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 33 publications
3
33
0
1
Order By: Relevance
“…However, there are limited data concerning the impact of the CIE in clinical practice. A previous study by our group dealt with this issue regarding the CIE, but the study failed to prove its clinical implications [18,25]. In this study, we demonstrated that the CIE was associated with treatment failure of MSSA bacteraemia when the patients were treated with cefazolin.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…However, there are limited data concerning the impact of the CIE in clinical practice. A previous study by our group dealt with this issue regarding the CIE, but the study failed to prove its clinical implications [18,25]. In this study, we demonstrated that the CIE was associated with treatment failure of MSSA bacteraemia when the patients were treated with cefazolin.…”
Section: Discussionmentioning
confidence: 53%
“…The CIE of MSSA isolates obtained from the cases was measured as described elsewhere [19,25]. Briefly, the cefazolin MICs obtained with a high inoculum (HI,~5 Â 10 7 CFU/mL) were compared with those obtained with a standard inoculum (SI,~5 Â 10 5 CFU/mL) to identify the strains with CIE, which was defined as an increase in the MIC to !16 mg/mL with a high inoculum from the susceptible range of the MIC with a standard inoculum [19].…”
Section: Measurement Of the Cefazolin Inoculum Effectmentioning
confidence: 99%
“…This study may have been underpowered to show such differences. Another report described 303 cases of MSSA bacteraemia and demonstrated that cefazolin may be used successfully in high-inoculum infections if the isolate is sensitive to either clindamycin or erythromycin [21]. Our analysis demonstrated that fewer patients on cefazolin stopped therapy due to adverse events than those receiving ASP, although only four trials were included.…”
Section: Figurementioning
confidence: 80%
“…This study may have been underpowered to show such differences. Another report described 303 cases of MSSA bacteraemia and demonstrated that cefazolin may be used successfully in high‐inoculum infections if the isolate is sensitive to either clindamycin or erythromycin .…”
Section: Discussionmentioning
confidence: 99%
“…In our review, the prevalence of β-lactamase ranges from 77 to 92% while Type A represents 15-34% and a cefazolin inoculum effect was found in 13 to 58% of the MSSA isolates. It seems that no significant association exists between inoculum effect positivity and demographic factors, underlying disease or site of infection [17] even though one study found that osteomyelitis is highly associated with cefazolin inoculum effect in South American hospitals [14]. Five studies assessed the clinical outcomes of the patients from whom MSSA isolates were collected depending on the presence of an inoculum effect.…”
Section: A Inoculum Effectmentioning
confidence: 99%